INDICATIONS FOR MORPHOMETRIC PARAMETERS OF THE CRANIOFACIAL REGION OF ELDERLY PEOPLE WITH PARTIAL AND COMPLETE ADHESION - N.B.Nurov (Scholar Express Journals, 2022)
As a consequence of advances in medicine, the average life expectancy in highly developed countries has increased significantly. At the same time, the number of elderly and old people is increasing as a percentage of the entire population, and probably in the third millennium more than 40% of the population will be people over 60 years old. Dental care systems should be guided by the changed demographic situation, it is necessary to develop a strategy in providing assistance to this part of the population. A high level of knowledge of the peculiarities of the oral cavity and effective methods of therapeutic and preventive dental care in the elderly population will improve the dental status and, consequently, the quality of life of this population group
Keywords: population; part; improve; peculiarities